Metabolomics approach to investigate the ergogenic effect of Morinda citrifolia L. leaf extract on obese Sprague Dawley rats - Abdul Majid, Nordiana; Abdul Hamid, Azizah; Salleh, Syafiq Zikri; Saari, Nazamid; Abas, Faridah; Pak Dek, Mohd Sabri; Ramli, Nurul Shazini; Jaafar, Ahmad Haniff (John Wiley and Sons, 2019)
Introduction: Natural products are obtaining much acceptance as ergogenic aid, not only among athletes but also among the general population including people with excess body fat. Under normal circumstances, an obese person will have the desire and ability to exercise reduced; mainly because they are easily fatigued. Thus, they need to boost their energy production so that they can be more active and healthier.